AETA 2013: Recent Advances in Electrical Engineering and Related Sciences - Zelinka, Ivan.; Duy, Vo Hoang; Cha, Jaesang; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
Over the past decades, fault diagnosis (FDI) and fault tolerant control strategies (FTC) have been proposed based on different techniques for linear and nonlinear systems. Indeed a considerable attention is deployed in order to cope with diverse damages resulting in faults occurrence.
From the Contents: Analysis of Electron Transport Coefficients in CF3I-N2 Mixture Gas Using an Electron Swarm Study -- TLSR: A Tree Link State Routing for Infrastructure-based Mobile Ad Hoc Networks -- Multi-Receive Antenna with Selection Combining Technique and Its Real-Time FPGA Implementation for Improvement in Spectrum Sensing.
Keywords: Engineering; Telecommunication; Production of electric energy or power; Engineering; Power Electronics, Electrical Machines and Networks; Mechatronics; Control; Communications Engineering, Networks